Knowledge and practices of parents about child eye health care in the public sector in Swaziland - Velibanti N. Sukati; Vannesa R. Moodley; Khathutshelo P. Mashige (AOSIS, 2018)
Background: Swaziland, like many other developing countries, lacks appropriate eye health services, particularly for children. Aim: To determine the knowledge and practices of parents about child eye health care in the public sector in Swaziland. Setting: The setting for this study was Swaziland. Methods: A descriptive study involving cross-sectional sampling methodology and quantitative analysis was employed with 173 randomly selected parents whose children attended public schools in Swaziland. Results: Out of 173 participants, 104 (60.1%) parents reported that they have never taken their children for an eye test and 69 (31.7%) felt that their children's vision was fine. Ninety-seven (53.1%) parents indicated having no knowledge about child eye conditions and no significant association was found between level of education and knowledge of eye conditions affecting children (p = 0.112). Having an immediate family member who wore spectacles increased the likelihood of a child being taken for eye testing (p = 0.001), but decreased the likelihood of being well informed about eye health (p = 0.218). Of those parents who reported taking their children for eye tests, 34 (49.3%) reported that they were given eye drops and 31 (44.9%) stated that their children were prescribed spectacles. Eighty-seven (50.3%) parents accepted the idea of their children wearing spectacles. Conclusion: The findings of the study suggest the need for parents to be informed about basic child eye health care and the importance of their children having regular eye examinations.